2021
DOI: 10.3390/nano11051200
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Carbon and Silver Inks for Wearable Applications

Abstract: For wearable electronic devices to be fully integrated into garments, without restricting or impeding movement, requires flexible and stretchable inks and coatings, which must have consistent performance and recover from mechanical strain. Combining Carbon Black (CB) and ammonia plasma functionalized Graphite Nanoplatelets (GNPs) in a Thermoplastic Polyurethane (TPU) resin created a conductive ink that could stretch to substrate failure (>300% nominal strain) and cyclic strains of up to 100% while maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 36 publications
(119 reference statements)
1
27
0
Order By: Relevance
“…The carbon inks have a significantly higher sheet resistance despite their similar thickness to the silver counterparts, because of the significantly higher bulk conductivity properties of silver. The sheet resistance of both the carbon and silver ink are in good agreement with the authors' previous work demonstrating the repeatability of the ink production and the screen-printing process [22]. This allows for the design of a printed heater where the significantly more conductive silver ink is used to uniformly deliver current to the heat generating resistive carbon heater block.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The carbon inks have a significantly higher sheet resistance despite their similar thickness to the silver counterparts, because of the significantly higher bulk conductivity properties of silver. The sheet resistance of both the carbon and silver ink are in good agreement with the authors' previous work demonstrating the repeatability of the ink production and the screen-printing process [22]. This allows for the design of a printed heater where the significantly more conductive silver ink is used to uniformly deliver current to the heat generating resistive carbon heater block.…”
Section: Resultssupporting
confidence: 86%
“…The white light images of single layer carbon (Figure 3a) and the single layer silver (Figure 3c) show no significant patterning on the surface of the coatings, suggesting that both inks were able to flow through the screen and relax to form a smooth coating, showing their suitability for screen printing. In a previous work by the authors Scanning Electron Microscope images to examine the microstructure of the coatings produced by the inks used in this study showed a near homogeneous surface, with the GNP flake size shown to be 4.05 ± 0.89 µm the smaller silver flakes appear to form a less homogenous microstructure, with voids present in the structure (Figure 3e,f) [22]. This relatively poorer particle distribution is a potential cause for the higher roughness in the silver print.…”
Section: Thicknessmentioning
confidence: 49%
See 2 more Smart Citations
“…Thermoplastic polyurethane (TPU) is widely used in the electronic industry owing to its outstanding chemical resistance, excellent flexibility, elasticity and processability [1][2][3][4]. Therefore, TPU has great application potential in thermal interface materials (TIMs), which play a crucial role in efficient thermal management [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%